Analisis Persetujuan Lingkungan Sektor Perumahan Terkait Dokumen UKL-UPL Dan Dampak Lingkungan - Ashfiyak Nur Hamid; R. Mohammad Alghaf Dienullah (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Environmental licensing in the housing sector plays an important role in ensuring that housing development is carried out in compliance with applicable environmental regulations. With the rapid development of the housing sector, it is important to ensure that licensing is carried out with sustainability principles that take into account the impact on the environment. This article examines the role of environmental licensing in the housing sector, the challenges faced in its implementation, and the importance of a sustainable approach to the licensing process to encourage environmentally friendly development